Penerapan Metode Tartil dalam Meningkatkan Kemampuan Membaca Al Qur’an Santri Pondok Pesantren Ath-Thohiriyyah Banyumas - Syafiul Anam, Ahmad; Misbah, M. (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This thesis aims to examine the application of the Tartīl method in improving the ability to read the Qur'an of students at the Ath Thohiriyyah Purwokerto Islamic Boarding School. Learning to read the Qur'an properly and correctly is a fundamental aspect in Islamic boarding school education, especially in forming religious competence in accordance with the rules of tajwid, makhārijul ḥurūf, and tartil rhythm as recommended in QS. Al-Muzzammil verse 4. The research method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that the Tartīl method has been applied continuously since the early 2000s on the initiative of the boarding school caretaker. Activities are carried out every Sunday morning after the Subuh prayer, starting with prayer and tawassul together, followed by individual reading of verses, direct correction by the ustadz, and collective repetition of readings. The application of this method plays a role not only as a means of reading practice, but also as an evaluative instrument and character building through discipline, perseverance, and mutual respect among students. The supporting factors include the charismatic leadership of the boarding school caretaker, the pedagogical competence of the ustadz, the religious climate of the boarding school, and the internal awareness of the students. Meanwhile, the main obstacles come from the limited physical readiness of students in the morning and variations in reading ability between individuals.